The impact of the use of cooperative learning in the achievement of sixth grade students Jerusalem in mathematics - Sanaa, Amraish; Alnahoui, Attahar (Milev Journal of Research and Studies, 2019)
The current research aims to study the impact of the use of collaborative learning in the collection of students of the sixth grade primary school mixed elementary school in mathematics. In order to achieve the objective of the research, the researcher put the following hypothesis: There were no statistically significant differences between the average number of students who studied mathematics using cooperative learning and the average number of students who studied mathematics in the traditional way. (49) students representing students of two divisions of the class For the academic year 2017/2018The researcher used the experimental design of two equal groups, where the sample chose the intended method and measured it into the first experimental groups that taught mathematics using collaborative learning and the second control, which is taught in the traditional way. And then parity between them in the variables of the student's age, grade of all grades and grade in mathematics in the sixth grade average level of education for his parents ,For the sixth grade in the public schools, as well as a statistical test in the first and second chapters of the mathematics book itself and according to its coefficient of stability. The two groups studied for six weeks. After the completion of the teaching, the test was conducted for the sample students. The results indicated that there were statistically significant differences between the average of the students who studied mathematics using cooperative learning and the average number of students who studied mathematics in the traditional way for the experimental group, In light of the results of the study, the researcher recommended using cooperative learning in teaching and suggesting similar studies to be studied in other classes and stages.